Correlation between microneutralization test and a multiplexed immunoassay for evaluation of monkeypox and vaccinia virus antibodies before and after smallpox vaccination - Marchi, Serena; Piccini, Giulia; Remarque, Edmond J.; Roscia, Giulia; Semplici, Bianca; Cantaloni, Paolo; Guerrini, Noemi; Zannella, Roberta; Coluccio, Rosa; Benincasa, Linda; Solfanelli, Niccolò; Trombetta, Claudia Maria; et al. (Frontiers in Immunology, 2025)
IntroductionMonkeypox (mpox), an endemic zoonotic viral disease in Central and Western Africa, gained international attention in 2022 when clade IIb of the Monkeypox virus (MPXV) spread outside Africa, prompting the World Health Organization (WHO) to declare it a Public Health Emergency of International Concern (PHEIC). Although the PHEIC was lifted in 2023 due to declining global cases, a resurgence caused by clade Ib has reinstated the emergency status. Current mpox vaccines, based on live-attenuated or modified vaccinia virus (VACV), have historical use in smallpox prevention. Understanding the humoral immune response triggered by mpox vaccination and infection, as well as identifying correlates of protection, remain however critical.MethodsIn a previous study, we evaluated the neutralizing antibody response of 1,000 individuals, half born before the cessation of smallpox vaccination in Italy (pre-1975) and half after (post-1979). Higher neutralizing antibody titers against MPXV and VACV were observed in subjects vaccinated against smallpox, indicating a cross-reactive immunity to MPXV. This study further investigated these findings by analyzing the IgG response to five MPXV and five VACV antigens in a subset of the previously tested cohort, using a multiplex immunoassay. Serum samples from 370 individuals were grouped by neutralization profile (negative for both MPXV and VACV, positive for both viruses, negative for MPXV but positive for VACV, and vice versa) and age (born before 1975 and after 1979).ResultsOur data revealed stronger immune responses to specific antigens, particularly A35R/A33R and B6R/B5R, with MPXV-specific binding antibodies showing greater cross-reactivity compared to VACV ones. Furthermore, individuals born before 1975, vaccinated against smallpox, exhibited stronger binding and neutralizing antibody responses, as opposed to people born after 1979 in whom neutralization titers were lower. This suggests that prior VACV-vaccination and subsequent boosting from potential other OPXV encounters in the older population may have resulted in a more VACV-specific immune response over time.DiscussionThis study provides insights into the antigenic determinants of MPXV and VACV antibody cross-reactivity and highlights differences in immune profiles across age and exposure groups. Results obtained suggest that VACV-vaccine imprinting shapes immunity, which could guide the development of more effective vaccine strategies for preventing mpox.